Seasonal Variations in Physico-Chemical Parameters of Vellar River, Vellar Estuary and Portonovo Coastal Waters, South East Coast of India - C, Prabhahar. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In the present study, hydro biological characteristic features of the Vellar river, Vellar estuary and Portonovo coastal water samples were collected from 3 sampling stations for the period of 6 months in both monsoon and summer seasons (2005-2006). The Physico-chemical factors like pH, temperature, EC, alkalinity, hardness, Chloride nutrients such as PO4, NO3, SO4, TDS, DO, BOD and COD were estimated by the samples. The overall analysis, it was observed that the fluctuations in the Physico-chemical parameters of water samples. The Vellar estuary daily has been facing the problems of municipal sewage, industrial wastes and anthropogenic activities etc.